Similarities of general and legal phraseologies in German. (Eurasian Journal of Learning and Academic Teaching, 2023)
This academic article will explain the similarities and differences between general and legal phraseologies in German. In addition, a detailed overview with examples of similarities and differences between general and legal phraseologies will be created